A noção de democracia na obra de Carlos Nelson Coutinho como intelectual e militante - Braz, Danielle Cristina (2016)
Understanding how was the construction of the concept of democracy in the political scientist Carlos Nelson Coutinho work is the central objective of this work. But through the analysis of this question, as many topics and discussions intertwine, making the thought of Coutinho, their aspirations and struggles are also the object of study. Because it is an intellectual who was also an activist of the political parties and social causes, we chose to make a time frame that values the participation of Coutinho in parties to which was attached: PCB, PT and PSOL, starting the first chapter in the 60s, when the author writes his first works and also gives the first steps as a young communist, and ending in 2012, with the last texts written by the author. The analysis method was inspired by the method developed by Michel Lowy to analyze the work of Lukacs and its central category itself Lukacsian idea of totality. The results show that the left history in Brazil and intellectual trajectory and Coutinho policy are intertwined and form a complex whole. All this, erects a peculiar notion of democracy that reflects the contradictions in our own training and also in the construction of Carlos Nelson Coutinho, while intellectual in constant motion.